Occurrence of Newcastle Disease and Infectious Bursal Disease Virus Antibodies in Double-Spurred Francolins in Nigeria. (18th November 2014) - Oluwayelu, Daniel Oladimeji; Adebiyi, Adebowale Idris; Olaniyan, Ibukunoluwa; Ezewele, Phyllis; Aina, Oluwasanmi
Abstract : The double-spurred francolin Francolinus bicalcaratus has been identified as a good candidate for future domestication due to the universal acceptability of its meat and its adaptability to anthropogenically altered environments. Therefore, in investigating the diseases to which they are susceptible, serum samples from 56 francolins in a major live-bird market (LBM) in Ibadan, southwestern Nigeria, were screened for antibodies against Newcastle disease (ND) and infectious bursal disease (IBD) viruses. Haemagglutination inhibition (HI) test and enzyme-linked immunosorbent assay (ELISA) revealed 25.0% and 35.7% prevalence of ND virus (NDV) antibodies, respectively, while 5.4% and 57.1% prevalence of IBD virus (IBDV) antibodies was detected by agar gel precipitation test (AGPT) and ELISA, respectively. This first report on the occurrence of NDV and IBDV antibodies in apparently healthy, unvaccinated double-spurred francolins from a LBM suggests that they were subclinically infected with either field or vaccine viruses and could thus serve as possible reservoirs of these viruses to domestic poultry. Furthermore, if they are to be domesticated for intensive rearing, a vaccination plan including ND and IBD should be developed and implemented.